Effects of respiratory muscle endurance training in hypoxia on running performance - Katayama, K.; Goto, K.; Ohya, T.; Iwamoto, E.; Takao, K.; kasai, N.; Sumi, D.; Mori, H.; ishida, K.; Shimizu, K.; Shiozawa, K.; Suzuki, Y. (Medicine & Science in Sports & Exercise, 2019)
Purpose We hypothesized that respiratory muscle endurance training (RMET) in hypoxia induces greater improvements in respiratory muscle endurance with attenuated respiratory muscle metaboreflex and consequent whole-body performance. We evaluated respiratory muscle endurance and cardiovascular response during hyperpnoea and whole-body running performance before and after RMET in normoxia and hypoxia.